Delay of routine health care during the COVID-19 pandemic: A theoretical model of individuals' risk assessment and decision making. (August 2022) - Shukla, Prakriti; Lee, Myeong; Whitman, Samantha A.; Pine, Kathleen H.
Abstract: Delaying routine health care has been prevalent during the COIVD-19 pandemic. Macro-level data from this period reveals that U.S. patients under-utilized routine health care services such as primary care visits, preventative tests, screenings, routine optometry care, dental appointments, and visits for chronic disease management. Yet, there is a gap in research on how and why patients understand risks associated with seeking or delaying routing health care during an infectious disease pandemic. Our research addresses this gap based on semi-structured interviews with 40 participants living in regions across the United States. By building upon Unger-Saldaña and Infante-Castañeda's model of delayed health care, we extend this model by articulating how health care delays happen during an infectious disease pandemic. Specifically, we show how perceptions of uncertainty and subjective risk assessments shape people's decisions to delay routine health care while they operate at two levels, internal and external to one's social bubble, interacting with each other. Highlights: During COVID-19, people delayed their routine health care due to various risks. Interplays between internal and external factors lead to risk assessment. One's perception and assessment of uncertainty and risk lead to health care delay. The availability of alternative health care may moderate one's risk assessment. We propose a new model of decision-making to delay health care.